Innovative Strategies for Enhancing Advanced Speaking Skills in Elementary School Learners - Al Husnah Mutmainah; Hamzah, Rahma Ashari; Asriati, Asriati (Universitas Islam Lamongan, 2025)
Speaking is a key skill that helps kids grow socially and academically in elementary school. This study looks into good ways to teach speaking, finds common problems, and suggests new solutions to help students improve their speaking skills. The study uses library research to gather information from many academic papers. It finds that methods like acting out roles, telling stories, and using interactive media help students speak better by making them more involved, confident, and clear when sharing their ideas. For example, storytelling helps students tell stories in a clear way, and role-playing helps them feel more connected and speak more smoothly by acting out real-life situations. But there are some problems, like students not being confident enough, using their own local language instead of standard English, and not using a wide range of media. To fix these, the study suggests new ideas, like using picture boards and digital tools, which have helped students speak more fluently and take part more in class discussions. These results add to the conversation about how well people can communicate and give teachers real ideas for teaching speaking in a way that’s fun and includes everyone. By focusing on communication and putting students first, this research shows how important it is to use methods that are based on real-life situations and encourage active participation in speaking at the elementary level.